Accountability of the ECB and a government's incentives to rebel against the common monetary policy in EMU - Olli Castrén (Bank of Finland, 1999)
This paper considers how the "true" common monetary policy that is conducted by the ECB under various sources of uncertainty will differ from the policy that was agreed in the Maastricht Treaty, and how the uncertainties may induce a representative government to criticise the common monetary policy.Acquiring information about the transmission mechanism, and revealing that information as well as information about the ECB reaction function, is incentive compatible for the ECB both directly and indirectly.The direct effect means that the ECB's own welfare is decreasing in uncertainties.The indirect effect arises because less uncertainty reduces the risk of criticism from the individual governments' side.The risk of criticism is the larger, and consequently the indirect incentive to reduce uncertainty is the higher, the larger are the leftward shifts in national political preferences from those that prevailed when the Maastricht Treaty was signed.The model also provides an explanation for the ECB's choice of monetary policy strategy that incorporates elements of both monetary targeting and inflation targeting.
URN:NBN:fi:bof-20140807106
Keywords: 330; Monetary uncertainty; monetary strategy; EMU